2021
DOI: 10.1016/j.phrs.2020.105224
|View full text |Cite
|
Sign up to set email alerts
|

Natural product derived phytochemicals in managing acute lung injury by multiple mechanisms

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(144 citation statements)
references
References 434 publications
(536 reference statements)
1
121
0
Order By: Relevance
“…Curcumin is a multipotential compound from C. longa that possesses diverse medicinal properties. It is a potent anti-inflammatory agent that is effective against numerous chronic diseases [ 14 , [440] , [441] , [442] , [443] ].…”
Section: Curcumin and Covid-19mentioning
confidence: 99%
“…Curcumin is a multipotential compound from C. longa that possesses diverse medicinal properties. It is a potent anti-inflammatory agent that is effective against numerous chronic diseases [ 14 , [440] , [441] , [442] , [443] ].…”
Section: Curcumin and Covid-19mentioning
confidence: 99%
“…Non-intoxicating CBD is a phytocannabinoid isolated from the Cannabis sativa plant [ 13 , 14 ] and, apart from the psychoactive ∆ 9 -tetrahydrocannabinol (THC), represents the best-studied compound in this group.…”
Section: Cannabidiol—pharmacological Potential and Mechanism Of Acmentioning
confidence: 99%
“…Nonetheless, the antiviral drug remdesivir shortens hospitalization time and the glucocorticoid dexamethasone even reduces mortality [ 10 , 11 ]. In addition, it is suggested that alternative compounds, including phytochemicals and natural agents targeting coronavirus development directly or as a result of their immunomodulatory effects, could be applied as potential therapies and for the prevention of COVID-19 [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional source for modern pharmaceutical discovery and potential drug leads, natural products have played an integral role in treating patients due to their unique structural, chemical, and biological diversity [ 1 , 2 , 3 ]. The current race to identify efficacious drugs, natural products with promising therapeutic effects has attracted significant attention, especially for the prevention and treatment of lung diseases, such as pulmonary fibrosis [ 4 ], asthma [ 5 ], acute lung injury [ 6 ], chronic obstructive pulmonary disease [ 7 ], defective pulmonary innate immunity [ 8 ], coronavirus disease 2019 (COVID-19) [ 9 ], and lung cancer [ 10 ]. Among the myriad of known lung maladies, COVID-19 and lung cancer are currently the most important public health concerns and burdens worldwide [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%